Brain-derived neurotrophic factor but not beta-secretase 1, vascular endothelial growth factor, glial fibrillary acidic protein and interleukin-1β correlate with cognitive impairment in adult persons with epilepsy: a cross-sectional single-center study from India - Kamini Bhavsar; Manjari Tripathi; Jyotirmoy Banerjee; Arpna Srivastava; Nidhi; Shivam Pandey; Divya Vohora (Frontiers in Neurology)
ObjectivesThis study aims to evaluate cognitive impairment utilizing the Montreal Cognitive Assessment (MoCA) scale, while also exploring the correlation between cognitive impairment and various serum biomarkers, including Brain-derived neurotrophic factor (BDNF), Beta Secretase-1 (BACE1), Vascular Endothelial Growth Factors (VEGF), Glial fibrillary acidic protein (GFAP), and Interleukin-1 (IL-1β) in adults living with epilepsy.MethodsIn this study, 74 participants aged between 18 and 50 years, who were visiting neurology outpatient consultations, were included. The cognitive assessment was executed using the MoCA test. Serum levels of BDNF, BACE1, VEGF, GFAP, and IL-1β were evaluated through ELISA in patients with and without cognitive impairments. To determine the association between MoCA scores and the biomarkers, both Spearman and Pearson correlation analyses, as well as linear regression, were conducted.ResultsAmong the 74 PWE, 61 exhibited cognitive impairment as determined by the MoCA assessment. Noteworthy alterations were detected across various MoCA subscales, encompassing visuospatial and executive functions, attention, language, abstraction, and delayed recall, with statistical significance established (p < 0.05). Furthermore, it was revealed that those in the cognitively impaired group presented with reduced serum BDNF levels (p < 0.05). It is important to highlight that no substantial differences were identified in the serum concentrations of BACE-1, VEGF, GFAP, and IL-1β. A moderate and statistically significant correlation was established between BDNF and the Total MoCA score (p < 0.05), in addition to BDNF’s relationship with Visuospatial & Executive function (p < 0.05). In the context of regression analysis, BDNF demonstrated a significant association to the Total MoCA score (p < 0.05), a connection that persisted as significant even when adjusted for confounding factors.ConclusionWe conclude that adult PWE in India demonstrate a significant cognitive impairment. Further, our findings indicate that BDNF may serve as a potential biomarker for evaluating cognitive impairment in adult PWE. Further longitudinal, prospective and multi-center studies are required to confirm the same.